G70(P) Reducing unnecessary blood taking in the NICU – a quality improvement project. (May 2019) - McDermott, H; Smith, A; Nath, P
Abstract : Aims: Iatrogenic blood loss from blood sampling is one of the key drivers for anaemia in unwell or preterm neonates. We report on a quality improvement initiative piloted in one neonatal intensive care unit (NICU) in the UK to establish blood taking practices and investigating ways in which to safely reduce unnecessary losses. Methods: A prospective 4 week period of data collection using a standardised proforma was completed. Following result analysis, a guideline for blood sampling and using the point of care gas machine results was introduced. These changes were evaluated by a subsequent 2 week period of prospective data collection using patient notes, online laboratory results and the same proforma. Results: See table 1 . The initial audit demonstrated that only 18% of tests resulted in or directly monitored a change in clinical management. It also showed that the point of care gas machine was sufficiently reliable to be used for commonly requested tests, when in the normal range, using Bland Altman analysis. The audit post-guideline showed that the number of laboratory tests significantly reduced, the mean number of tests acted upon to produce a change in clinical management doubled from 18% to 36% and the calculated cost of laboratory tests per patient reduced by £3.50. Conclusion: This shows the successful implementation of a quality improvement project to reduce blood testing, in a small sample, in a NICU.